Management of urethral stricture: High‐pressure balloon dilation versus optical internal urethrotomy. Issue 2 (9th November 2017) - Kumano, Yohei; Kawahara, Takashi; Mochizuki, Taku; Takamoto, Daiji; Takeshima, Teppei; Kuroda, Sinnnosuke; Teranishi, Jun‐ichi; Makiyama, Kazuhide; Miyoshi, Yasuhide; Yumura, Yasushi; Yao, Masahiro; Uemura, Hiroji
Abstract : Objective: Urethral stenosis is a disease in which the lumen of the urethra becomes constricted by fibrosis. Such stenoses have been treated by urethral dilation using a bougie and optical internal urethrotomy (OIU). Recently, high‐pressure balloon dilation (BD) has been developed as a new treatment method for urethral stenosis. The present study compared the effectiveness of urethral dilation by BD and OIU. Methods: Twenty‐two patients of urethral stenosis were treated at Yokohama City University Medical Center between 2005 and 2015. Of these, 13 underwent BD, whereas OIU was performed in 9. BD was performed at 30 atm twice for 5 min each time. In OIU, an endoscopic knife was used to cut out the stenotic lesion in 3 directions. The endpoint was set as restenosis, which required additional surgical treatment, including BD, OIU, and the use of a urethral bougie. Results: The causes of urethral stricture were endoscopic surgery (n = 7; 31.8%), development after total prostatectomy (n = 4; 18.2%), iatrogenic reasons associated with catheter insertion (n = 5; 22.7%), development after a prostate needle biopsy (n = 3; 13.6%), and unknown (n = 3; 13.6%). The site of the stenotic lesion site was the anastomosis (n = 3; 13.6%), bladder neck (n = 6; 27.3%), prostatic urethra (n = 4; 18.2%), anterior urethra (n = 7; 31.8%), and membranous urethra (n = 2; 9.1%). The stenosis‐free rate was 84% for those undergoing BD and 22% for those receiving OIU. The median stenosis‐free time was significantly longer after BD than OIU (1675 vs. 244 days, respectively; P  < .01). Conclusion: The stenosis‐free time was significantly longer after BD than OIU.